Advances in upconversion luminescence nanomaterial‐based biosensor for virus diagnosis. Issue 6 (12th October 2022) - Ma, Yingjin; Song, Menglin; Li, Lihua; Lao, Xinyue; Wong, Man‐Chung; Hao, Jianhua
Abstract: Various infectious viruses have been posing a major threat to global public health, especially SARS‐CoV‐2, which has already claimed more than six million lives up to now. Tremendous efforts have been made to develop effective techniques for rapid and reliable pathogen detection. The unique characteristics of upconversion nanoparticles (UCNPs) pose numerous advantages when employed in biosensors, and they are a promising candidate for virus detection. Herein, this Review will discuss the recent advancement in the UCNP‐based biosensors for virus and biomarkers detection. We summarize four basic principles that guide the design of UCNP‐based biosensors, which are utilized with luminescent or electric responses as output signals. These strategies under fundamental mechanisms facilitate the enhancement of the sensitivity of UCNP‐based biosensors. Moreover, a detailed discussion and benefits of applying UCNP in various virus bioassays will be presented. We will also address some obstacles in these detection techniques and suggest routes for progress in the field. These progressions will undoubtedly pose UCNP‐based biosensors in a prominent position for providing a convenient, alternative approach to virus detection. Abstract : This review discusses the recent advancement in the upconversion nanoparticle (UCNP)‐based biosensors for virus and biomarkers detection. We summarize four basic principles that guide the design of UCNP‐based biosensors, which are utilized with luminescent or electric responses as output signals. Relative strategies with a detailed discussion are presented, and we suggest routes for progress in the field.